Nikita Brat - bohater literacki czy filmowy? "Brat, strelaj pervym" Władimira Kołyczewa i jego analogie z twórczością Aleksieja Bałabanowa = Nikita Brat - a literary or film hero? "Brat, strelaj pervym" by Vladimir Kolyczev; the analogies with Aleksiej Balabanov`s works - Kalita, Liliana (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The text concentrates on Vladimir Kolyczov, a contemporary Russian writer, and the inspiration he drew from Aleksiej Balabanov`s film "Brat" (1997). This Russian cult picture of perestroika became an inspiration for the novel series ?Brat? (2000-2006). The author analyzes the first part of the series since it relies the most on the pattern presented by Balabanov`s feature film.
Keywords: kino rosyjskie; Bałabanow, Aleksiej (1959-2013); Kołyczew, Władimir (1968- ); proza rosyjska; mafia rosyjska; 20 w.; 21 w.; Russian cinema; Russian mafia; Russian prose